2005
DOI: 10.1016/j.ijid.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment and the diagnosis of Streptococcus pneumoniae in lower respiratory tract infections in adults

Abstract: The diagnosis of infection with S. pneumoniae is very dependent on whether or not recent (within 2-4 weeks) or immediate (within 48 hours) antibiotic treatment has been given prior to microbiological sampling of patients. The results suggest an optimized diagnostic strategy with, if possible, sampling for culture prior to antibiotic treatment, while sampling for pneumococcal antigens should wait 24-48 hours for antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The present authors have previously demonstrated that the present urinary antigen test is more often positive in those pre-treated than in those not pre-treated with antibiotics [14]. Thus, mPCR and the urinary antigen test appear useful in patients treated with antibiotics, in order to identify S. pneumoniae in patients who will probably give false negative results in their cultures.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The present authors have previously demonstrated that the present urinary antigen test is more often positive in those pre-treated than in those not pre-treated with antibiotics [14]. Thus, mPCR and the urinary antigen test appear useful in patients treated with antibiotics, in order to identify S. pneumoniae in patients who will probably give false negative results in their cultures.…”
Section: Discussionmentioning
confidence: 51%
“…Silkeborg County Hospital is the only hospital in the region and serves a basic population of 100,000 inhabitants in the area. As previously described [14], all immunocompetent adult patients hospitalised for LRTI during weekdays between September 1997 and August 2000 were consecutively included in the present study. Thus, the included patients were unselected adult patients with LRTI requiring hospitalisation.…”
Section: Study Subjectsmentioning
confidence: 99%
“…There are many pneumonia treatments available, such as antibiotics, breathing treatments, and oxygen therapy (Korsgaard et al 2005; van der Poll and Opal 2009). However, people with weak immune systems are likely to have complications such as respiratory failure, uncontrolled inflammation (i.e., sepsis), and lung abscesses (CDC 2017).…”
Section: Pneumoniamentioning
confidence: 99%
“…L. pneumophila serogroup 1 antigen detection in urine is the most rapid method to diagnose or exclude the infection. A negative test makes legionella unlikely, but does not exclude legionella infection’ [A3] [209,214–242].…”
mentioning
confidence: 99%